Seizure aggravation by ampicillin/sulbactam in an elderly patient with status epilepticus - Kaoru Obata; Masako Kinoshita; Akiyo Shinde; Toshihiko Suenaga (International Journal of Emergency Medicine)
Abstract Background Ampicillin/sulbactam (ABPC/ SBT) is one of the most common β-lactam antibiotics for patients with status epilepticus complicated with aspiration pneumonia. It is known that β-lactam antibiotics such as penicillin aggravate epileptic seizures or status epilepticus. Here, we investigated whether ABPC/SBT aggravates seizures using electroencephalography (EEG) monitoring. Case presentation An 84-year-old male with status epilepticus who presented with a new onset of clonic seizures mainly of his left side and underwent continuous video EEG was analyzed. He had been suffering from severe ulcerative colitis and infectious enteritis, delirium, atrial fibrillation and deep venous thrombosis. His cerebrospinal fluid analysis was unremarkable. Four days after starting levetiracetam, he had a cluster of seizures with impaired consciousness, consistent with status epilepticus. We started fosphenytoin and phenobarbital. We also administered ABPC/SBT twice a day, ten times in total, for aspiration pneumonia while monitoring the patient. He died twelve days after the seizure onset. We analyzed the number and duration of seizures in two hours before and after starting ABPC/SBT for each administration using EEG with trendgraph. After administration of ABPC/SBT, number of seizures significantly increased from 3.2 ± 4.7 to 7.3 ± 9.7 (mean ± SD, p = 0.047, Wilcoxson’s signed-rank test) per 2 h. Duration of seizures showed a tendency of increase from 199 ± 275 to 406 ± 536 s (p = 0.079). Conclusions In this elderly male patient with status epilepticus, administration of ABPC/SBT aggravated his seizures. EEG monitoring using a trendgraph is useful for evaluation of seizure severity and for analysis of causative factors.